Legal Interpreting in Spain at a Turning Point - Blasco Mayor, María Jesús; Pozo Triviño, Maribel del (MonTi Monografías de Traducción e Interpretación, 2016)
The publication in the European Union of Directive 2010/64/EU of the European Parliament and of the Council of 20 October 2010 on the right to interpretation and translation in criminal proceedings has been a turning point in a great number of aspects related to court and police interpretation. The main objective of the Directive is to ensure quality legal interpretation throughout the process, as part of the right to defence and to a fair trial. Spain, as a Member State of the EU, has the obligation to transpose this European Directive into its domestic law. Therefore, this is a historic moment in which two main factors converge: the need to change the legislation to bring it in line with the new Directive and the need to implement measures to ensure compliance with new mandates. This paper reviews the present state of legal interpretation in Spain from the point of view of legislation and that of service provision and analyses the measures that Spain should take to ensure that court and police interpretations are carried out with due guarantees. These measures include the training of interpreters and legal operators, the creation of accreditation systems and records, as well as the consolidation of the professional profile of interpreters.